Enhancing Fourth-Grade Students' Learning Outcomes Using Rabdology Board Media in Elementary Mathematics Education - Andriana Rosda; Rahayu Condro Murti; Marwan Marwan; Agus Herwanto; Agustian Agustian; Sigit Wibowo (STAI Hubbulwathan Duri, 2025)
Improving students' learning outcomes in mathematics, particularly multiplication, remains a challenge in elementary education. This study investigates the effectiveness of the rabdology board as a visual and interactive learning tool to enhance the multiplication skills of fourth-grade students at SD Negeri 16 Panjak, West Kalimantan. A combination of quantitative and qualitative approaches was used. The intervention included introducing the rabdology board, demonstrating its use, providing directed practice, facilitating group discussions, and evaluating student learning outcomes. Data were collected through learning outcome tests and classroom observations. Findings indicate a significant improvement in students' multiplication learning outcomes, increasing from 58% to 80% after using the Rabdology Board. Additionally, students demonstrated higher motivation and active engagement in learning. The study highlights the effectiveness of interactive and visual teaching aids in enhancing students’ comprehension and engagement in mathematics. The rabdology board provided a structured approach that facilitated faster multiplication calculations and improved conceptual understanding. The rabdology board is an effective tool for improving multiplication learning outcomes in elementary students. Its integration into mathematics education can serve as an alternative strategy to enhance student performance and engagement. Further research could explore its application in other mathematical concepts and educational settings.